(untitled) (Medical Forum Monthly, 2024)
Objective: to determine the risk factors and clinical features in the young-onset stroke belonging to the rural areas. Study Design: Retrospective, Observational. Place and Duration of Study: This study was conducted at the Department of Neurology, Medical Unit II, Peoples Medical College Hospital, Nawabshah from 1.1.2006 to 31.12.2006. Materials and Methods: Hospital records of acute stroke cases aged 20-45 years were reviewed. Stroke was defined according to the WHO criteria. Demographic and clinical data including the risk factors were scrutinized. Laboratory investigations and the CT Scan of brain were evaluated in all cases. Results: Twenty-cases were documented. Male= 12 (60%), Female= 8(40%). Age ranged from 20-45 years. Majority were uneducated and they were residents of small rural communities. Hypertension was the most frequent risk factor in 13 (65%) of cases (Table 1). Only 2 (10%) were previously taking antihypertensive treatment while 18 (90%) were not receiving any treatment prior to stroke. Heart disease was present in 2 (10%). Three (15%) were smokers. One (5%) had Diabetes mellitus, 3 (15%) had previous stroke and 1 (5%) had a family history of stroke. Three (15%) had none of the above risk factors. Hemiplegia was the most common presentation where 8 (40%) had right while 7(35%) had left hemiplegia and in 5 (25%) sidedness could not be ascertained because of deep coma (Table 2). Glasgow Coma Scale (GCS) ranged from 5-12 out of 15. Cerebral infarction was more common 12 (60%) than cerebral haemorrhage 6 (30%) while in 2 (10%) CT findings were unremarkable (Table 3). Of the 20 cases 3 (15%) expired and 17 (85%) survived (Table4). Fatal cases had GCS of below 8 out of 15. Conclusions: This study indicates that hypertension is the major risk factor for stroke in young adults belonging to the rural areas. Hemiplegia was the most common presenting feature. Cerebral infarction accounts for 60% of the cases and the survival rate was 85%. Unawareness and poor control of hypertension appears to be the main reasons behind the young-onset stroke in our region.